(untitled) (KULT_online, 2016)
This book examines how the ruling parties in Croatia and Slovakia in the 1990s made use of history in politics in order to gain and maintain power. The politics of history and nationalist ideologies developed by the Croatian Democratic Union (Hrvatska demokratska zajednica – HDZ) and the Movement for Democratic Slovakia (Hnutie za demokratické Slovensko – HZDS) are analysed against the backdrop of historical legacies, political contexts, and the dissolution processes of Czechoslovakia and Yugoslavia, respectively. Apart from a number of differences, the comparison reveals considerable similarities that could be useful in explaining the presence or absence of a democratic deficit in countries that held the position of ˈjunior partnersˈ in the socialist federations of Yugoslavia, Czechoslovakia, and the Soviet Union.